Measuring and optimizing the input technical effectiveness and efficiency of production processes by means of the linear programming method - Donini, Benito Romeo (Technovation)
Linear programming (Simplex method) has been applied to two real industrial cases to optimize the input technical effectiveness and efficiency of production processes. The procedure is simple, reliable and useful for obtaining data and information about the degree of efficiency achieved in production processes, so as to carry out techno-economic analyses and, consequently, to modify the way of managing a process or the process itself, if necessary.